Hubungan Konsep Diri dengan Perilaku Bullying Pada Remaja Di UPT SMP Negeri 6 Pangsid - nur fiqry ardinar; Meriem Meisyaroh; Muhammad Ardianto Rodin (Infomasi dan Promosi Kesehatan, 2024)
Background: Self-concept is one way of looking at patterns of behavior towards oneself in the environment and society. Self-concept is very important because it influences how a person behaves, especially in adolescents because adolescence is a transition stage from childhood to adulthood. A good or positive self-concept means having better behavioral well-being, and vice versa, a bad or negative self-concept means having less good behavior. Self-concept plays an important role in the dynamics of bullying because bullying behavior occurs because there is a poor self-concept, so that those who feel better will bully those who feel less, this often happens in schools because in reality in schools bullying behavior often occurs and develops So there are many trends on social media about bullying behavior in teenagers. Method: The type of research used is quantitative using analytical descriptive methods, the number of samples in this research was 41 respondents with a sampling technique using total sampling, the tools used were questionnaire sheets and data analysis using Univariate and Bivariate Analysis. Result: The results of the research show that the self-concept possessed by the students of UPT SMP Negeri 6 Pangsid is a good self-concept as many as 32 respondents with a percentage (78.0%) and bullying behavior is in the low category as many as 38 respondents with a percentage (92.7% ). There is a significant relationship between self-concept and bullying behavior in adolescents with a p value of 0.001 < 0.05.